Sistem Pendukung Keputusan Pemilihan Bibit Pada Lahan Pasir Berlempung Menggunakan Metode Moora - Muhammad Farhan Rizki; Berto Nadeak; Henry Kristian Siburian (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2022)
Serdang Bedagai Regency is one of the areas that has become a rice barn in North Sumatra Province. However, in recent years, rice production in Serdang Bedagai Regency, especially in Lubuk Bayas Village, has decreased. Some of the causes for the decline in productivity levels of crop yields in recent years are caused by erratic weather conditions, unfavorable land, many pests and diseases, and farmers are still based on habits and experience in choosing seeds. In this study, the Multi-Objective Optimization on The Basis of Ratio (Moora) method was applied with the aim of providing the best solution in selecting rice seedlings on sandy loam land (Case Study: Lubuk Bayas Village, Perbaungan District). Based on the criteria set by Lubuk Bayas Village used in this study, namely: plant age, yield potential, resistance to pests, resistance to disease, and productive tillers. This aims to make it easier to choose rice seeds on sandy loamy soils that are superior, so that later the resulting system using a web-based programming language can further assist Lubuk Bayas Village in determining the selection of rice seeds on sandy loamy soils (Case Study: Lubuk Bayas Village Perbaungan District). The results of the ranking values for superior rice seeds obtained in the study show that it is known that alternative A7 rice seeds, namely rice seeds, can be proposed as superior seeds from the results of the selection carried out with a value of 0.3766.